Anelastic spectroscopy in Al2O3 - Grandini, Carlos Roberto [UNESP]; Oliveira, R. L N [UNESP]; Mota, Rogério Pinto [UNESP]; Santos, F. P.; Campos, E. (Trans Tech Publications Ltd, 2005)
Engineering ceramics have found use in many applications, such as engine parts, ball bearings, artificial bone and hip replacements and gyroscopes, because of their good chemical inertness, hardness, high temperature stability and excellent wear resistance. Oxide ceramic may meet these demands. Alumina (Al2O3) ceramics offer a high potential for many engineering applications, such as wear- and/or corrosion-resistant components, and as material for substrates or housings in microelectronic devices. Alumina is used among other things for seal ring, draw-cones, guides, water mixing tapes, bearing parts, medical prostheses and cutting tools. Measurements of the elastic energy loss and modulus (anelastic spectroscopy) as a function of temperature can distinguish among the different atomic jumps, which occurs in the various phases or at different local ordering. In this paper, it is reported anelastic relaxation measurements in Al2O3 samples using commercial starch. These measurements were carried out in a torsion pendulum operating in frequencies around 40 Hz. The results shown strongly influence of the type of forming in the elastic modulus obtained by anelastic relaxation measurements.
Keywords: Al2O3; Elastic modulus; Mechanical spectroscopy; Starch consolidation; Ball bearings; Ceramic materials; Elastic moduli; Microelectronics; Wear resistance; Alumina